# 3y+6=27

### 19 Answers | Add Yours

I agree with frizzyperm--we can't do your homework for you. But here is how, in general to do this type of question.

Remember that because there is an "=" sign, it means that whatever you do to one side of the equation you can do to the other, because that's what "equal" means. So for number 1, see if there is something you can do so that you only have the term with an unknown (the letter) in it. Aha, you can subract 6 from each side of the equation. That leaves you with 3y=27; if you divide each side by 3, you will get what y equals.

y=7

At what point does 'helping students learn' become 'doing students' homework for them' ????

Q1.) move the +6 to the right side of the equation, making it -6, so **3y = 27-6** and then continue

Q2) **5(b-6)** is equal to **5b - 30**

... +7b .... gives **12b - 30 = 12**

move the -30 to the right side gives **12b = 42**

x = ?

Q3) 3x +17 = 11x -13

move -13 to the left side...

3x +17 +13 = 11x

3x +30 = 11x

30 = 8x

? = x

3y + 6 = 27

Solution;

3y = 27 - 6

3y = 21

y = 21/3

y = 7

Hence solved....

To check whether the answer is right....

Insert the value of y in the equation...

3y + 6 = 27

3 (7) + 6 = 27

21 + 6 = 27

27 = 27

LHS = RHS

hence the answer is right...

3y+6=27

In order to solve this equation we need to isolate the ones which cannot be calculated to one side, in this case y.

3y=27-6

3y=21

y=21/3

**y=7**

3y + 6 = 27

I'm going to assume we are solving for what y is so here we go.

First subtract 6 on both sides this will cancel out the 6 on the left side and leave you with the 3y

(3y + 6) -6 = (27) - 6

3y = 21

Now divide the 3 from the 3y on both sides of the equation and the 3 on the left side will cancel out and you will get the y by itself.

3/(3y) = 3/(21)

y=7

**Equation:**

3y+6=27

3y+(6-6)=27-6

3y=21

3y/3=21/3

**y=7**

3y + 6 = 27

To get " y " alone you have to subtract 6 from both sides

Subtracting the 6 on both side would make the equation into

3y = 27 now you just divide 3 on both side

Dividing 3 on both sides would make the equation into

y = 29 which is your answer

3y+6=27

3y= 21 subtract 6 from both sides

y=7 divide both sides by 3

It's a fairly simple technique we are here to help of course but in the future in college you might not find answers right away on hard problems so I would say engrave this in your mind

3y+6=27

Since you need to find y move the numbers on one side

3y=27-6

Divide by 3

y=21/3

y=7

3y+6=27

When solving for a variable, we have to undo what is being done.

The first operations we can undo are addition and subtraction. In this case we can undo the addition by subtracting 6 from both sides to get :

3y = 21

The next operations we can undo are multiplication and division. In this case we can undo the multiplication by dividing 3 from both sides to get :

y = 7

3y+6=27

3y+6=27

3y+6=27

3y+6-6=27-6

3y=21

y=7

3y+6-6=27-6

3y/3=21/3

y=7

You could think about it this way:

3 times something PLUS 6 will give me 27.

Work it backwards and subtract the 6. That gives you 21.

Now think: What times 3 will give me 21?

y must equal 7 (y=7)

Sometimes, reason will help you solve problems better than formulas or rules.

bleah, that serves me right for pointing out other people's mistakes...

you got number *three ***right! **

@ Bmaruffi

sorry, but...

you got number one wrong.

you got number two wrong.

and you got number four wrong.

but you got number two **right**!

1. subtract six from six as well as 27 (this is called combining like terms) this will give you 3y=21. Then divide 3 into 3y as well as 27. This will give you 9 or y=9

2. distribute 5 into (b-6) through multiplication. This will give you 5b-6+7b=12. combine like terms 5b+7b. This will give you 12b=12. Now divide 12 from both sides. This will give you 1 or b=1

3. Realize that the like terms are on opposite sides of the equals sign so you have to use the opposite signs. Subtract the smaller number from the larger number...Start by subtracting 3x from itself as well as 11x. This will give you 17=8x-13. Now continue combining like terms and add 13 from itself as well as 17. This will give you 30=8x. Now divide 8 from 8x as well as 30. this will give you 3.75=x.

4. First cross multiply. 1(8x+110) and 5(10x+130) This will give you 8x+110=40x+650. Now combine like terms...remember to use the opposite sign because they are on different sides of the equals sign. Subtract 8 from itself as well as 40x This will give you 110=32x+650. Now subtract 650 from itself as well as 110. This will give you -540=32x. Now divide 32 from itself as well as 540. This will give you -16.875=x.

Good